PENGUKURAN PANJANG PLASTIK ROL BERBASIS MIKROKONTROLLER AT Mega 8535 - Setyadjit, Kukuh; Hariadi, Balok (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2015)
The development of a microcontroller system in the control system more advanced, more and enable people to perform the control of a device automatically without a computer device. This makes the control systems in various industries increasingly easy and cheap. In this study will be made of plastic cutting machine control system roll sensor-based optocoupler. This tool uses two dc motors, one as a driver to roll up the plastic so that the plastic to form a roll (a roll), and other dc motor to move the heater (seal) and cutter. For the heating process (seals) used a wire niklin while cutting process using a saw blade. Untukmenentukan long pieces of plastic then used an optocoupler sensor and microcontroller ATmega16 as the main control center.Kata kunci : Mikrokontroller AT Mega 8535